Pengaruh Akupresure PC6 dengan Aromaterapi Lemon terhadap Kejadian Mual dan Muntah Pada Ibu Hamil Trimester I dengan Hiperemesis Gravidarum di Wilayah Puskesmas Karangtengah Cianjur Tahun 2023 - Dede Aris Herdiansyah; Rina Afrina; Sri Mintasih (NAJ Nursing Applied Journal, 2024)
Hyperemesis Gravidarum is excessive nausea and vomiting during pregnancy, more than 8 times in 24 hours or at any time which can cause symptoms of dehydration, electrolyte imbalance and weight loss. The nature and level of nausea and vomiting can vary, from mild to severe. One of the first alternatives is PC6 acupressure, while the second alternative is using lemon aromatherapy. Objective: To determine the effect of PC6 acupressure therapy with lemon aromatherapy on the frequency of nausea and vomiting in first-term pregnant women with hyperemesis gravidarum in the Cianjur Community Health Center area in 2023. Method: This research is a type of quasi-experimental research with a two group comparison pretest-posttest design. The sampling technique used purposive sampling with a total research sample of 30 respondents. Results: research from post-test measurements P-Value = 0.001 Independent Sample T-Test Ho was rejected and the sample supported the existence of a significant influence. Conclusion: There is an effect of PC6 acupressure with lemon aromatherapy on the incidence of nausea and vomiting in first trimester pregnant women with hyperemesis gravidarum in the Karangtengah Cianjur health center area in 2023.